ANALISA VEGETASI HUTAN RIPARIAN DATARAN RENDAH DITEPI SUNGAI NGGENG, TAMAN NASIONAL KAYAN MENTARANG, KALIMANTAN TIMUR - Purwaningsih, Purwaningsih (BERITA BIOLOGI, 2009)
Study on the riparian forest of Nggeng River bank at Kayan Mentarang National Park was carried out with quadrate method. It would cover species composition and vegetation structure. The results of a floristic inventory of trees with DBH e" 10 cm in a lowland riparian forest of Nggeng river side show that 106 species, consist of 53 genera and 29 families in the plot of 2 hectare sampled. The two leading families in terms of number of species were Dipterocarpaceae and Myrtaceae while according to the total sum of importance values were Dipterocarpaceae and Fabaceae. The common species in two plots were Saraca hulletii, Parashorea parviflora, Dipterocarpus oblongifolius, Castanopsis motleyana, and Dryobalanops lanceolata. The diversity of the river-side were lower than the other forest in Kalimantan and in north is more rich of species than south plot. The forest type on the river side were shown mixed dipterocarp forest, because the forest dominated by dipterocarps species. Forest structure on the sides of Nggeng River were shown there were some emergent trees, they are up to 45 m tall and in diameter >100 cm. Some emergent trees in the location were such as Parashorea parviflora, Dipterocarpus oblongifolius and Shorea spp. Lists on the most 10 leading family trees, 10 leading family saplings, density, frequency and important values of each inventory plants species are provided.